Do innovative firms communicate more? Evidence from the relation between patenting and management guidance - HUANG, Sterling (Institutional Knowledge at Singapore Management University, 2020)
Successful innovations could induce more disclosure if the information asymmetry between the firm and its investors about post-innovation outcomes leads investors to demand more information. However, such innovations also likely entail greater proprietary cost concerns, which deter disclosure. This paper uses patent grants to examine the effect of innovation success on management guidance behavior. We find that more management guidance follows patent grants, suggesting that despite disclosure cost concerns, firms with successful innovations do respond to information demand. This association is stronger after enactment of Regulation Fair Disclosure and for firms with greater institutional investor ownership, further highlighting the role of information demand. The association is weaker for firms with more competition, consistent with proprietary cost concerns having a moderating impact. Overall, our findings suggest that innovation creates demand for more voluntary disclosure and firms’ disclosure decisions following innovation outcomes vary in ways that disclosure theory and economic intuition predict.